Kemampuan Guru Menggunakan Metode Penilaian Autentik Berbasis Proyek dalam Pembelajaran Teks Genre Faktual pada Kelas VII SMPN di Kecamatan Sekongkang Kabupaten Sumbawa Barat - Rizanty; Mahsun; Burhanuddin (Jurnal LENTERA: Jurnal Studi Pendidikan, 2022)
This study aims to determine 1). How is the application of authentic assessment using a project-based scientific approach in learning Indonesian, 2). What is the form of an authentic assessment instrument in learning that uses a project-based scientific approach, 3). How is an authentic assessment model that uses a project-based scientific approach that is applied by teachers in learning Indonesian for class VII at a State Junior High School in Sekongkang District, West Sumbawa Regency? This type of research uses the descriptive analysis method, where the researcher analyzes the data associated with the implementation of imperative pragmatics. The data obtained using the method of tests, projects, reports and documentation, field notes compiled by the researcher, and the results of the data are presented in the form of a narrative description. From the research results obtained. 1. The application of authentic assessment using a project-based scientific approach, namely the preparation process for the assessment carried out by the teacher is very good. While the application of authentic assessment according to data about the time and method of assessment obtained from respondents, the answers given by each teacher are, there are differences but the final results show good results. 2. The form of an authentic assessment instrument is that the teacher gives daily questions or quizzes to test the extent to which students' abilities can understand factual genre text teaching materials. In addition, the teacher also gives project-based assignments to students before the teaching and learning process is carried out. 3. Authentic assessment model using tests and non-tests. The test given is based on factual genre text material delivered by the Indonesian language teacher. In the non-test assessment model, the teacher gives a project to students at the beginning of the lesson and then collects it according to a predetermined time